DNA Isolation from Whole Blood Samples of Endometriosis Patients using the Salting out Method and ITS Scope in Ayurveda - Lakshmi (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: As time goes on, more methods and resources for assessing patients’ health will become available. Another developing area of science is personalized medicine. Any nucleated cell, including blood, tissue, hair, etc., can have its human DNA retrieved. High protein content and a range of secondary metabolites present in various sources affect DNA purification; highly pure DNA is necessary for molecular study. Here, we extracted a considerable amount of human DNA from endometriosis patients’ whole blood using the salting out procedure. This is a cheap, quick, safe, and simple method. Research facilities and medical laboratories may make use of it. Objectives: The objectives of the study were (1) to isolate the DNA from the blood of endometriosis patients to conduct a whole-exome sequencing analysis aimed at learning more about the genetic variations connected to the disease and (2) to evaluate the scope of this technique in Ayurveda in endometriosis diseases. Materials and Methods: A 5 ml blood sample of diagnosed cases of endometriosis was collected from Sir Sunder Lal Hospital, Banaras Hindu University in a heparinized vial from Obstetrics and Gynaecology OPD. Extraction of DNA will be done in the Centre for Genetic Disorders, Institute of Science, and Banaras Hindu University. Conclusion: Using the Salting Out method, good quality DNA samples from human whole blood can be extracted that is enough to perform a Whole Exome Sequencing.